The changing epidemiology of shigellosis in Australia, 2001-2019. - Aaliya F Ibrahim; Kathryn Glass; Deborah A Williamson; Benjamin G Polkinghorne; Danielle J Ingle; Rose Wright; Martyn D Kirk (Public Library of Science (PLoS), 2023)
Shigellosis is an increasing cause of gastroenteritis in Australia, with prolonged outbreaks reported in remote Aboriginal and Torres Strait Islander (hereafter "First Nations") communities and among men who have sex with men (MSM) in major cities. To determine associations between Shigella species and demographic and geographic factors, we used multivariate negative binomial regression to analyse national case notifications of shigellosis from 2001 to 2019. Between 2001 and 2019, Australian states and territories reported 18,363 shigellosis cases to the National Notifiable Diseases Surveillance System (NNDSS), of which age, sex and organism information were available for >99% (18,327/18,363) of cases. Of the cases included in our analysis, 42% (7,649/18,327) were S. sonnei, 29% (5,267/18,327) were S. flexneri, 1% (214/18,327) were S. boydii, less than 1% (87/18,327) were S. dysenteriae, and species information was unknown for 28% (5,110/18,327) of cases. Males accounted for 54% (9,843/18,327) of cases, and the highest proportion of cases were in children aged 0-4 years (19%; 3,562/18,327). Crude annual notification rates ranged from 2.2 cases per 100,000 in 2003 and 2011 to 12.4 cases per 100,000 in 2019. Nationally, notification rates increased from 2001 to 2019 with yearly notification rate ratios of 1.04 (95% CI 1.02-1.07) for S. boydii and 1.05 (95% CI 1.04-1.06) for S. sonnei. Children aged 0-4 years had the highest burden of infection for S. flexneri, S. sonnei and S. boydii; and males had a higher notification rate for S. sonnei (notification rate ratio 1.24, 95% CI 1.15-1.33). First Nations Australians were disproportionately affected by shigellosis, with the notification rate in this population peaking in 2018 at 92.1 cases per 100,000 population. Over the study period, we also observed a shift in the testing method used to diagnose shigellosis, with culture independent diagnostic testing (CIDT) increasing from 2014; this also coincided with an increase in notifications of untyped Shigella. This change in testing methodology may have contributed to the observed increase in shigellosis notifications since 2014, with CIDT being more sensitive than culture dependent testing methods. The findings of this study provide important insights into the epidemiological characteristics of shigellosis in Australia, including identification of high-risk groups. This can be used to inform public health prevention and control strategies, such as targeted communication programs in First Nations communities and places with high levels of interaction between young children, such as childcare centres. Our study findings also highlight the implications of culture independent testing on shigellosis surveillance, particularly a reduction in the availability of species level information. This emphasises the continued importance of culture dependant testing for national surveillance of shigellosis.